2017
DOI: 10.1111/eva.12481
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution of behaviour during independent host‐shifts following maize introduction into Asia and Europe

Abstract: Maize was introduced into opposite sides of Eurasia 500 years ago, in Western Europe and in Asia. This caused two host‐shifts in the phytophagous genus Ostrinia; O. nubilalis (the European corn borer; ECB) and O. furnacalis (the Asian corn borer; ACB) are now major pests of maize worldwide. They originated independently from Dicot‐feeding ancestors, similar to O. scapulalis (the Adzuki bean borer; ABB). Unlike other host‐plants, maize is yearly harvested, and harvesting practices impose severe mortality on lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The formation of the clines on the continents had been rapid. ACB and ECB made the host shift to maize independently around 500 years ago (Alexandre et al, 2013; Calcagno et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the clines on the continents had been rapid. ACB and ECB made the host shift to maize independently around 500 years ago (Alexandre et al, 2013; Calcagno et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the clines on the continents had been rapid. ACB and ECB made the host shift to maize independently around 500 years ago (Alexandre et al, 2013;Calcagno et al, 2017). The ECB cline in North America formed within 100 years since its introduction around 1920 (Showers et al, 1975;Sparks & Young, 1971).…”
Section: Repeated Use Of Permentioning
confidence: 99%
“…However, a few species, such as the two major polyphagous pests (European corn borer and Asian corn borer) shifted their primary host plants to monocots (e.g., Poaceae; Figs S2, S3). This result implies that these two morphologically indistinguishable species likely diverged recently in complete allopatry and shifted their host preference to maize, supporting the hypothesis that this may have occurred when its cultivation spread 500 years ago in Europe and East Asia (Gay, 1999; Coates et al ., 2005; Malausa et al ., 2007; Calcagno et al ., 2017). According to Léger et al .…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, it partly co-occurs with its sibling species, the European corn borer, Ostrinia nubilalis , which is a major pest of maize ( Zea mays ). Previous studies demonstrated that O. scapulalis and O. nubilalis are specialized to their respective host plants [2] , [3] , [4] , [5] , [6] , [7] and that their genetic divergence is rather low so that they can be considered as sibling species [8] . Yet, a few genomic sequences and rearrangements are much more divergent than the rest of the genomic background [1] , [9] , [10] , [11] .…”
Section: Datamentioning
confidence: 99%